2019
DOI: 10.1108/ijdi-12-2018-0198
|View full text |Cite
|
Sign up to set email alerts
|

Trends and determinants of socioeconomic inequalities in sexual and reproductive health among women in Ghana

Abstract: Purpose This study aims to estimate the degree and nature of socioeconomic-related inequalities in sexual and reproductive health in Ghana and further assesses causes of these inequalities using decomposition technique. The authors assess the contribution of personal characteristics of the woman including access to health information and health seeking behaviours, household and locational characteristics to inequalities in sexual and reproductive health in Ghana. The study uses data from the three rounds of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(75 reference statements)
0
2
0
1
Order By: Relevance
“…Although the fertility rates of most high-income countries are declining, the programs and interventions seem not to be working in many SSA countries as the rate of fertility is either stable, reducing at a slower pace, or is on the rise [8,[10][11][12]. For example, In Ghana it is reported that the TFR has been fluctuating over 2 decades [13,14]. Despite the introduction of many government policies, programs and interventions such as the 2004 National Population Policy, Ghana Population and AIDS project (1996)(1997)(1998)(1999)(2000), 2002 Free Compulsory Universal Basic Education (FCUBE) Contraceptive Social Marketing project (1987)(1988)(1989)(1990), Ghana Family Planning and Health Programme (1990Programme ( -1996 and Free Senior High School programs, TFR has not seen major declines and it remains unclear the trend over the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…Although the fertility rates of most high-income countries are declining, the programs and interventions seem not to be working in many SSA countries as the rate of fertility is either stable, reducing at a slower pace, or is on the rise [8,[10][11][12]. For example, In Ghana it is reported that the TFR has been fluctuating over 2 decades [13,14]. Despite the introduction of many government policies, programs and interventions such as the 2004 National Population Policy, Ghana Population and AIDS project (1996)(1997)(1998)(1999)(2000), 2002 Free Compulsory Universal Basic Education (FCUBE) Contraceptive Social Marketing project (1987)(1988)(1989)(1990), Ghana Family Planning and Health Programme (1990Programme ( -1996 and Free Senior High School programs, TFR has not seen major declines and it remains unclear the trend over the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…Skilled birth attendance rates vary across countries, with some regions experiencing low rates [6] . Postnatal care utilization is also variable, with some studies reporting low rates of utilization [7,8] .…”
Section: Household Reproductive Health Characteristicsmentioning
confidence: 99%
“…Hasil ini sejalan dengan penelitian di Ghana. Penelitian tersebut menginformasikan bahwa wanita usia subur di Ghana yang memiliki status sosioekonomi lebih baik memiliki kemungkinan yang lebih tinggi untuk menggunakan alat kontrasepsi, terutama jenis alat kontrasepsi modern (Agyire-Tettey et al, 2019). Penelitian sebelumnya di Indonesia menemukan informasi yang sejalan.…”
Section: Pembahasanunclassified